PENGARUH PRICE SENSITIVITY DAN TIME SENSITIVITY TERHADAP REPURCHASE INTENTION DI MEDIASI SATISFACTION PADA FOLLOWERS INSTAGRAM (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of app-based food delivery services in Indonesia has intensified competition among platforms, including ShopeeFood. In this competitive landscape, price and service speed are key factors influencing consumers' platform choices, making it essential to understand how price sensitivity and time sensitivity affect customer satisfaction and repurchase intention. This study aims to analyze the effect of price sensitivity and time sensitivity on repurchase intention with satisfaction as a mediating variable among ShopeeFood users who follow the official Instagram account @shopeefood_id in Bekasi. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire from 180 respondents who met the research criteria. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that price sensitivity and time sensitivity have a positive and significant effect on satisfaction. Furthermore, satisfaction has a positive and significant effect on repurchase intention. However, price sensitivity and time sensitivity do not have a significant direct effect on repurchase intention. The indirect effect analysis shows that satisfaction fully mediates the relationship between price sensitivity and repurchase intention, as well as between time sensitivity and repurchase intention. Therefore, customer satisfaction plays a crucial role in enhancing repurchase intention in ShopeeFood services.